The application of nanostructural foil for diffusion welding of composite based on aluminum alloy 6061 containing 55 % SiC - Bugaenko, B. V.; Buturlia, Y. A.; Kvasnitskiy, V. V.; Kvasnitskiy, V. F.; Korzhik, V. N.; Бугаєнко, Б. В.; Бутурля, Е. А.; Квасницький, В. В.; Квасницький, В. Ф.; Коржик, В. Н. (My University, 2018)
The process of diffusion welding in vacuum (DWV) of an aluminum-based composite using nano-multilayer aluminum–nickel and aluminum–titanium foils is investigated. Aluminum alloy 6061 hardened silicon carbide (55 at.%). It has low ductility, which makes deformation activation of the surfaces being joined difficult. Therefore, DWV perform through the intermediate layer, for example, aluminum foil. In this work, the layers obtained by the method of electron beam deposition were used. In layers with alternating nanolayers with rapid heating, reactions of self-propagating high-temperature synthesis take place, in which the amount of generated heat is sufficient for additional heating of the composite and it’s melting, which ensures activation of the surfaces to be joined. At the first stage, the creep processes of the composite under DWV conditions are investigated, the parameters and the creep equation are determined, as well as the allowable deformations that do not cause cracks. For DWV, Al/Ni and Al/Ti foils with thicknesses of 20, 40, 50, and 94 microns were used. The effect of the thickness of the interlayers on the formation of compounds has been established. It is shown that, regardless of the interlayer system, at the majority of the junction metal has a composite structure with common grains and the boundary between the connected samples is not determined either by structure or by chemical analysis.
Дифузійне зварювання композиту на основі алюмінієвого сплаву 6061, що містить 55 % SiC з використанням наноструктурної фольги
The application of nanostructural foil for diffusion welding of composite based on aluminum alloy 6061 containing 55 % SiC = Дифузійне зварювання композиту на основі алюмінієвого сплаву 6061, що містить 55 % SiC з використанням наноструктурної фольги / B. V. Bugaenko, Y. A. Buturlia, V. V. Kvasnitskiy, V. F. Kvasnitskiy, V. N. Korzhik // Shipbuilding & Marine Infrastructure. – 2018. – № 2 (10). – P. 214–221.
Keywords: сomposite; nano-layered foil; creep; self-propagating high-temperature synthesis; chemical composition; microhardness